Analisa Tindak Tutur Ilokusi Dalam Pertunjukan Stand-Up Komedi Trevor Noah Yang Berjudul 'Afraid of the Dark' - Houtandi, Cecillia Noveline; Adrallisman (Fakultas Sosial dan Humaniora - Universitas Buddhi Dharma, 2024)
Humor contains various components that lend itself to the study of language. This study focuses on the usage of illocutionary speech acts in Trevor Noah's